ANALISIS FAKTOR YANG MEMPENGARUHI KEINGINAN KONSUMEN BERBELANJA ONLINE MELALUI KEPERCAYAAN KONSUMEN - Prasetya, Adhitya Yoga (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
Consumerâs perception of online shopping risk, convenience and usefulness distinctly affects consumerâs trust as well as consumerâs acceptance behavior of online shopping. Therefore, this paper puts forward a consumerâs trust antecedents model based on TAM to explain online shoppers` behavior, in which consumerâs trust plays a core role. The result shows that consumerâs online shopping intention is decided by trust, perceived usefulness and perceived risk of online shopping, and consumerâs trust depends on consumerâs perceived risk, perceived ease of use and perceived usefulness of B2C E-commerce.